Loans in Colonial and Modern Nahuatl. A Contextual Dictionary - Brylak, Agnieszka (Trends in Linguistics. Documentation [TiLDOC], 2020)
The dictionary expands on the original idea of Karttunen and Lockhart to map the usage of loans in Nahuatl, by using a much larger and diversified corpus of sources, and by including contextual use, missing in earlier studies. Most importantly, these sources enrich the colonial corpus with modern data - significantly expanding on our knowledge on language continuity and change.